Experimental investigation on the impact resistance of rubber self-compacting concrete. (May 2022) - Chen, Jianxing; Zhuang, Jinping; Shen, Sizheng; Dong, Shuqing
Abstract: Stiffness degradation and micro-cracks are commonly observed in the self-compacting concrete subjected to long-term vibration and impact loading. Adding rubber particles to the concrete is a universal approach to improve impact resistance. Exploiting the dynamic mechanical properties of the rubber self-compacting concrete under impact loading is of great significance. Herein, a comprehensive investigation of rubber self-compacting concrete under impact loading was carried out using a split Hopkinson pressure bar. The influence of rubber replacement rate, rubber particle size, and strain rate on impact resistance was considered. 108 rubber self-compacting concrete specimens along with 36 ordinary self-compacting concrete ones were designed. As a result, the dynamic stress–strain relationship of rubber self-compacting concrete was proposed. The results show that rubber self-compacting concrete's dynamic peak strain and peak stress were higher than ordinary self-compacting concrete with similar static compressive strength. The dynamic compressive strength and DIF-σ and DIF-ε of rubber self-compacting concrete can be increased with strain rate. The sensitivity of growth rates of DIF-σ and DIF-ε to strain rate decreases with the strain rate. DIF-σ and DIF-ε showed a positive linear correlation with rubber content. The increase of rubber content reduces the dynamic compressive strength of rubber self-compacting concrete. Compared with other sizes, the dynamic compressive strength and DIF-σ and DIF-ε of 12 mesh (1 ∼ 2 mm) rubber particles are generally higher.